1977
DOI: 10.1029/jb082i002p00307
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Lg and lateral variations in crustal structure in Asia

Abstract: Lg propagates efficiently with predominant periods of about 1 to 1 1/2 s across the stable regions of Asia: the Indian shield, the Eurasian platform, the Tarim basin, and (less efficiently) eastern China. This suggests that the structure is relatively homogeneous and Q must be high in the crust in these regions. For paths across the Tien Shan, where the crust is abnormally thick, Lg is observed with somewhat less sharp arrivals, but nevertheless, frequencies are high, and amplitudes large. For paths along the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(77 citation statements)
references
References 13 publications
7
70
0
Order By: Relevance
“…-78- which L propagates very efficiently. These findings are similar to g those of Ruzaikin et al (1977).…”
Section: Seismograms With Unusual Characteristicssupporting
confidence: 81%
“…-78- which L propagates very efficiently. These findings are similar to g those of Ruzaikin et al (1977).…”
Section: Seismograms With Unusual Characteristicssupporting
confidence: 81%
“…The Lg waves have been modeled as higher-mode surface waves [Herrmann and Kijko, 1983] or as multiple reflected S waves [Campillo et al, 1984;Campillo, 1990], which propagate in the crust. The characteristics of the propagation of Lg waves have been discussed for many regions [e.g., Ruzaikin et al, 1977;Campillo and Plantet, 1991;Campillo et al, 1993;Chazalon et al, 1993;McNamara et al, 1996;Shi et al, 1996;Benz et al, 1997;Rial and Ritzwoller, 1997;Rodgers et al, 1997;Mellors et al, 1999;Calvert et al, 2000] and have been studied using numerical simulations [e.g., Kennett, 1986;Maupin, 1989;Regan and Harkrider, 1989;Cao and Muirhead, 1993;Gibson and Campillo, 1994;Kennett, 1997, 1998;Vaccari and Gregersen, 1998]. It has been observed that Lg propagation becomes inefficient or is blocked if the crustal structure undergoes fast lateral changes [Ruzaikin et al, 1977;Baumgardt, 1990;Campillo et al, 1993;Chazalon et al, 1993] or if the travel path crosses oceanic crust [Press and Ewing, 1952;Knopoff et al, 1979;Kennett et al, 1985;Gregersen and Vaccari, 1993;Shapiro et al, 1996].…”
Section: Introductionmentioning
confidence: 99%
“…Lg show inefficient propagation along paths that cross Tibet [Molnar and Oliver, 1969;Ruzaikin et al, 1977]. [Shih et al, 1973;York et al, 1976].…”
Section: Studies Of Sn Andmentioning
confidence: 99%